Mental toughness development and training in sport - Cowden, R. G.; Crust, L.; Tibbert, S. J.; Jackman, P. C. (Advances in mental skills training, 2021)
In the past two decades, the concept of mental toughness (MT) has been studied extensively by scholars and practitioners interested in the psychology of performance excellence. As the literature on MT has grown, resolution of early ambiguities surrounding the concept has led to improvements in conceptual clarity and increased consensus among researchers about its definition (Cowden, Crust, Joynt, Hook, & Worthington, 2018). Most scholars agree that MT represents a psychological resource that enables individuals to initiate and sustain efforts toward attaining optimal levels of performance despite exposure to adversity (e.g., Coulter, Mallett, & Gucciardi, 2010; Gucciardi, Hanton, Gordon, Mallett, & Temby, 2015; Hardy, Bell, & Beattie, 2014). As such, MT is a key psychological attribute associated with various indicators of success in sport (for a review, see Cowden, 2017a). In summary, MT has the potential to enhance sport performance and promote athletes` well-being. Although evidence has offered some support for the efficacy of selected MT interventions, current approaches require further empirical evaluation. Importantly, opportunities exist to examine the utility of currently unexplored avenues for developing MT among athletes. As sport personnel (e.g., coaches, practitioners) explore available approaches and implement MT training initiatives, careful consideration should be given to sport-specific contextual factors that are likely to affect the type, degree, and manner in which MT should be targeted and the short- and long-term implications of interventions that aim to nurture MT.